An Evaluation of the Effectiveness of Coenzyme Q10 Gel in Management of Patients with Chronic Periodontitis (II inter group comparison) - Taif M Salih; Maha Sh Mahmood (College of Dentistry/ University of Baghdad, 2016)
Background: Anti-oxidants are used as supplements to counteract the over production of free radicals in periodontal disease.Co-Q10 functions as an intercellular antioxidant by acting as a primary scavenger of free radicals (FRs) and reactive oxygen species (ROS), this study aimed to evaluate the effect of intra pocket application of perio Q gel (coenzyme Q10) alone and as adjunct to scaling and root planing on the periodontal clinical parameters in the treatment of patients with chronic periodontitis and compare the better improvement on the clinical periodontal parameters among different treatment modalities at 3 and 6 weeks. Materials and methods: A total of 323 sites with pocket depth (5-8) mm in patients with chronic periodontitis were randomly divided into three groups. The Gel group, 111 sites were treated with intra-pocket application of Perio Q gel alone. In the Combination group, 106 sites were treated with scaling and root planning (SRP) plus intra- pocket application of Perio Q gel, in Scaling and root planing group, 106 sites were treated with scaling and root planing alone. Clinical periodontal parameters such as Plaque index (PI), Gingival index (GI), Bleeding on probing (BOP), Probing pocket depth (PPD), Relative attachment level (RAL) were assessed at first visit, 3weeks and 6weeks. Results: Inter-group analysis, showed significant reduction in the clinical parameters PPD and RAL of combination group in comparison to SRP group. Conclusion: Better improvement of the clinical periodontal parameters had been achieved by using the gel in combination with scaling and root planing instead of using scaling and root planing only. Keyword: Chronic periodontitis, Antioxidants, Coenzyme Q10, Perio Q Gel